The narrative interview for the assessment of the assisted person: structure, method and data analysis - Artioli, Giovanna; Cosentino, Chiara; Taffurelli, Chiara; Ferri, Paola; Foà, Chiara (Acta Biomedica Atenei Parmensis, 2019)
Background and aim: If it is true that the impact of the symptoms of the disease is differently perceived by each person and that there is an incommunicability of the experiences of suffering, it is equally true that the narration provides an understandable representation, which derives from the network of representations that are part of a personal history.  The aim of this study was to offer an in-depth analysis of the “narrative interview” collected during the assessment of a 74 years old diabetic woman. Methods: A case study was conducted by a nurse with advanced expertise in conducting narrative interview. Content analysis and Meaning analysis were performed using a Grounded theory approach and according with Gee’s Poetic Method. Results: The patient after the diagnosis felt disbelief, anger and confusion. The illness forces her to change her life, habits and social role, with high suffering. However she adjusted to this new condition and thanks to her strong and positive attitude and the social support she received, she has succeeded in activating her “post traumatic growth”. Conclusions: A good narrative interview starts long before the interview itself and it requires: a specific training in the use of the instrument; the strengthening of specific skills (e.g. the active listening); the choice of optimal setting and timing for the patient; the ability to offer encouragement in the expression of the subjective experience and to conduct an analysis of the patient’s words with a subjective lens, reflecting the uniqueness of each illness experience.